Traditional Chinese medicine nano hydrogel for treating recurrent oral ulceration as well as preparation method and application of traditional Chinese medicine nano hydrogel

By introducing the ingredients of Jiaweidao Chisan into the hydrogel prepared by sodium alginate and chitosan, Jiaweidao Chisan iron nanocomposite hydrogel was prepared, which solved the limitations in the treatment of recurrent oral ulcers and achieved a more efficient and stable therapeutic effect.

CN119607085APending Publication Date: 2025-03-14FIRST HOSPITAL OF SHANXI MEDICAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411852508.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has limitations in the treatment of recurrent oral ulcers, including low local concentration of the drug, poor anti-infection ability, poor taste and unstable treatment effect.

Method used

The ingredients of odorous pyrosan were introduced into the hydrogel prepared by sodium alginate and chitosan to prepare odorous pyrosan iron nanocomposite hydrogel (FeNPs@DaochiSan hydrogel), which has high mechanical strength, stability, swelling ratio, adhesion time and antioxidant ability.

Benefits of technology

It improves the bioavailability, stability and targeting of the drug, improves patient compliance, enhances treatment effect, and overcomes the shortcomings of traditional Chinese medicine oral decoctions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607085A_ABST
    Figure CN119607085A_ABST
Patent Text Reader

Abstract

The invention discloses traditional Chinese medicine nano hydrogel for treating recurrent oral ulceration as well as a preparation method and application of the traditional Chinese medicine nano hydrogel, and belongs to the technical field of medicines. According to the preparation method disclosed by the invention, the modified daochiSan is introduced into hydrogel prepared from sodium alginate and chitosan to prepare the modified daochiSan iron nano composite hydrogel (FeNPs at DaochiSan hydrogel), and the hydrogel has the characteristics of high mechanical strength, strong stability, high swelling ratio, long adhesion time, oxidation resistance, biocompatibility and the like; by improving the bioavailability, the stability, the targeting property and the controlled release property of the medicine, the compliance of a patient is improved, the treatment effect is improved, and a new way is provided for the inheritance and the application of the traditional modified Daochi powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical materials, and in particular to a traditional Chinese medicine nano hydrogel for treating recurrent oral ulcers, and a preparation method and application thereof. Background Art

[0002] Recurrent oral ulcer (ROU), also known as recurrent aphthous ulcer (RAU), is the most common oral mucosal ulcer disease. At present, the etiology and related pathogenesis of ROU are not very clear clinically, and no specific method for curing ROU has been found. Therefore, the Western medicine treatment of ROU is currently mainly based on local symptomatic treatment, with the main purpose of alleviating the patient's pain, promoting ulcer healing and preventing secondary infection. The obvious and serious toxic and side effects of Western medicine limit their clinical application, and the ulcers of more and more patients tend to be stubborn, painful, recurrent, and short intervals. The effect of Western medicine on improving ROU symptoms is tolerant. In comparison, Chinese medicine treatment has the advantages of less toxic and side effects and tolerance. Therefore, the present invention innovatively develops a Chinese medicine preparation to contribute to the treatment of recurrent oral ulcers.

[0003] The self-prescribed prescription of Jiawei Daochisan (Daochisan plus Shigao decoction, composed of raw Rehmannia root, raw gypsum, Tongcao, raw licorice, and light bamboo leaves) has a significant effect in treating ROU. This prescription contains only five herbs and is strictly compatible. Animal experiments, clinical trials, and clinical applications have confirmed that this prescription has the effects of regulating immunity and anti-inflammatory. However, traditional Chinese medicine oral decoctions have the problems of cumbersome preparation, slow onset, and poor taste, so innovation of Chinese medicine preparations is urgent.

[0004] The emergence of nano-targeted technology has brought new directions to the research and development of traditional Chinese medicine for the treatment of various difficult and complicated diseases. Nanoparticles are small in size, large in surface area, and have a good surface area to volume ratio. They can better improve the local concentration, solubility and bioavailability of drugs, and can also protect drugs from damage by some basic environmental factors, thereby improving the stability and therapeutic effect of drugs. Summary of the invention

[0005] The purpose of the present invention is to provide a traditional Chinese medicine nano hydrogel for treating recurrent oral ulcers, and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art. The present invention introduces Jiawei Daochi San into a hydrogel prepared from sodium alginate and chitosan to prepare a Jiawei Daochi San iron nanocomposite hydrogel (FeNPs@DaochiSan hydrogel), which has the characteristics of high mechanical strength, strong stability, high swelling ratio, long adhesion time, antioxidant ability and biocompatibility. By improving the bioavailability, stability, targeting and controlled release of the drug, it improves patient compliance and improves the therapeutic effect, providing a new way for the inheritance and application of traditional Jiawei Daochi San.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] The present invention provides a method for preparing a traditional Chinese medicine nano hydrogel for treating recurrent oral ulcers, comprising the following steps:

[0008] (1) preparing flavored hematite nanoparticles;

[0009] (2) preparing sodium alginate solution and chitosan solution;

[0010] (3) After mixing the sodium alginate solution and the chitosan solution, add the solution of the flavored hematite nanoparticles to obtain a composite hydrogel solution, which is dried and formed to obtain the traditional Chinese medicine nano hydrogel.

[0011] Furthermore, the method for preparing the flavored hematite nanoparticles comprises the following steps:

[0012] a. Mix bamboo leaves, raw rehmannia root, tongcao, raw licorice root and raw gypsum in a mass ratio of (12-18): (8-12): (8-12): (4-8): (25-40) and grind into powder, dissolve the powder in boiling water to obtain a modified Daochi powder solution;

[0013] b. Mix the flavored red-dispersing powder solution and the FeCl3·6H2O solution in an ultrasonic bath for reaction, centrifuge, and dry to obtain the flavored red-dispersing powder iron nanoparticles.

[0014] Optionally, the concentration of the Jiawei Daochisan solution is 1.5-3 mg / mL; the concentration of the FeCl3·6H2O solution is 0.01-0.03 M; and the volume ratio of the Jiawei Daochisan solution to the FeCl3·6H2O solution is 10:(2-5).

[0015] Optionally, the temperature of the ultrasonic bath is 60°C-70°C, the time is 60-80 min, and the ultrasonic power is 200-250W.

[0016] Furthermore, the sodium alginate solution is obtained by mixing sodium alginate and water in a ratio of 1 g: (40-60) mL.

[0017] Furthermore, the chitosan solution is obtained by mixing chitosan, glacial acetic acid and water in a ratio of 1 g: (2-6) mL: (240-260) mL.

[0018] Optionally, the volume ratio of the sodium alginate solution and the chitosan solution when mixed is 1:1, and the mixing time is 25-40 minutes.

[0019] Optionally, the concentration of the flavored hematite nanoparticle solution is 1 mg / mL, and the added amount is 45-55 mL.

[0020] The invention also provides a traditional Chinese medicine nano hydrogel prepared by the preparation method.

[0021] The present invention also provides an application of the traditional Chinese medicine nano hydrogel in preparing a product for treating recurrent oral ulcers.

[0022] The present invention discloses the following technical effects:

[0023] The present invention prepares a cross-linked three-dimensional network hydrogel system constructed by Jiawei Daochisan, iron nanoparticles, FeCl3·6H2O, sodium alginate, chitosan, and glacial acetic acid. The hydrogel has the characteristics of strong stability, high swelling ratio, long adhesion time, antioxidant ability, and biocompatibility, and can provide a method for treating oral ulcers with better bioavailability, stability, targeting, and controlled release. It can overcome the limitations of the current oral ulcer gel dressings that are easy to fall off in the oral environment, poor anti-infection ability, and low local drug concentration, and achieve excellent therapeutic effects. The present invention innovatively introduces iron nanoparticles to make the overall structure of the hydrogel of the present invention more stable, with higher mechanical strength, and has the advantages of low cost, stable chemical properties, and simple preparation. Many metal nanomaterials have been proven to have enzyme-like activity. The hydrogel of the present invention also shows excellent potential in antibacterial, regulating body immunity, controlling reactive oxygen levels, and controlling oxidative damage. It is expected to become an ideal wound dressing for patients with recurrent oral ulcers and contribute to the treatment of traditional Chinese medicine in oral medicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The SEM image (A) and TEM image (B) of the FeNPs@DaochiSan particles of Example 1, the scale bar is 1:100 nm;

[0026] Figure 2 The particle size distribution diagram (A) and zeta potential (B) of FeNPs@DaochiSan particles in Example 1;

[0027] Figure 3 The SEM images of the hydrogels of Comparative Example 1 (A) and Example 2 (B), the scale bar is 1:100 nm;

[0028] Figure 4 is the porosity of the hydrogels of Comparative Example 1 and Example 2;

[0029] Figure 5 is the swelling ratio of the hydrogels of Comparative Example 1 and Example 2;

[0030] Figure 6 is the adhesion time of the hydrogels of Comparative Example 1 and Example 2;

[0031] Figure 7 The DPPH clearance test results of the hydrogels of Comparative Example 1 and Example 2;

[0032] Figure 8 is the hydrogen peroxide removal rate of the hydrogels of Comparative Example 1 and Example 2;

[0033] Fig. 9 is the nitric peroxide free radical scavenging rate of the hydrogels of Comparative Example 1 and Example 2;

[0034] Fig.10 These are the cytotoxicity test results of the hydrogels of Comparative Example 1 and Example 2. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] The biological materials and reagents involved in the embodiments of the present invention can all be purchased through conventional channels; the detection methods or calculation methods involved are all carried out using conventional methods in the art.

[0041] Example 1

[0042] This embodiment prepares a kind of flavored hematite nanoparticles, and the specific preparation process is as follows:

[0043] (1) Weigh 15 g of bamboo leaves, 10 g of raw rehmannia root, 10 g of tongcao, 6 g of raw licorice root, and 30 g of raw gypsum, mix them, crush and grind them into powder, add the powder into boiling water at a ratio of 0.2 g:100 mL, stir until the powder is dissolved, and prepare a modified Daochi powder solution;

[0044] (2) The Jiawei Daochisan solution was mixed with a 0.02M FeCl3·6H2O solution in a volume ratio of 10:3, stirred evenly with a magnetic stirrer, and then placed in an ultrasonic bath for full reaction for 70 min. The temperature of the ultrasonic bath was set to 65°C and the ultrasonic power was 225W.

[0045] (3) washing the reaction solution with a 50% ethanol solution, repeating the washing three times, centrifuging at 10,000 rpm for 15 min to separate the precipitate, and drying the precipitate in an oven at 45° C. to obtain black flavored iron nanoparticles (referred to as FeNPs@DaochiSan particles);

[0046] (4) The FeNPs@DaochiSan particles were structurally analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and their particle size and zeta potential were measured. Figure 1 and Figure 2 As shown, it can be seen that the FeNPs@DaochiSan particles are tightly bound, the particle size distribution is uniform, and the system is highly stable.

[0047] Example 2

[0048] This embodiment prepares a flavored hematite nanogel, and the specific preparation process is as follows:

[0049] (1) 0.5 g of sodium alginate was mixed with 25 mL of distilled water, and the mixture was stirred by a magnetic stirrer to obtain a sodium alginate solution;

[0050] (2) 0.1 g of chitosan was mixed with 0.5 mL of glacial acetic acid, and then 24.5 mL of distilled water was added, and the mixture was stirred with a magnetic stirrer to fully dissolve, thereby preparing a chitosan solution;

[0051] (3) The alginate solution and the chitosan solution were mixed in an equal volume ratio, stirred for 30 min, and then 50 mL of the FeNPs@DaochiSan particle solution (concentration of 1 mg / mL) prepared in Example 1 was slowly added to the mixed solution while stirring to obtain a uniform composite hydrogel solution;

[0052] (4) Pour the composite hydrogel solution and spread it evenly on a 5×5×4cm 3 The propylene box was placed in a 60°C drying oven and dried for 24 hours to form a traditional Chinese medicine nanocomposite hydrogel.

[0053] Comparative Example 1

[0054] This comparative example prepares a pure hydrogel, which differs from Example 2 only in that the FeNPs@DaochiSan particle solution in step (3) is omitted. The specific preparation process is as follows:

[0055] (1) 0.5 g of sodium alginate was mixed with 25 mL of distilled water, and the mixture was stirred by a magnetic stirrer to obtain a sodium alginate solution;

[0056] (2) 0.1 g of chitosan was mixed with 0.5 mL of glacial acetic acid, and then 24.5 mL of distilled water was added, and the mixture was stirred with a magnetic stirrer to fully dissolve, thereby preparing a chitosan solution;

[0057] (3) mixing the alginate solution and the chitosan solution in equal volume ratio and stirring for 30 min to obtain a uniform hydrogel solution;

[0058] (4) Pour the hydrogel solution and spread it evenly on a 5×5×4cm 3 The propylene box was placed in a 60°C drying oven for 24 hours to form a pure hydrogel.

[0059] Test Example 1

[0060] The hydrogels of Example 2 and Comparative Example 1 were subjected to structural characterization and performance testing, and the process was as follows:

[0061] 1. Scanning electron microscope image (SEM)

[0062] The results are as follows Figure 3 As shown, A is the SEM image of comparative example 1, and it can be seen that the surface structure of the hydrogel is relatively loose. B is the SEM image of Example 2, and it can be seen that after the addition of FeNPs@DaochiSan, the hydrogel morphology presents a cross-linked three-dimensional network structure and has a hollow structure with thin hollow walls, on which relatively uniform FeNPs@DaochiSan particles are attached. It can be seen that the overall structure of the gel in Example 2 is relatively loose, with a higher porosity and specific surface area, which may be related to its high swelling ratio, which can load more active ingredients, increase adhesion time, and provide a better biocompatible site for drug delivery and transportation.

[0063] 2. Porosity

[0064] The results are as follows Figure 4 As shown, the porosity of comparative example 1 is 79.77%, and the porosity of example 2 decreases slightly after adding FeNPs@DaochiSan, but still has a high porosity of 75.43%, and retains the characteristics of hydrogel, with a high drug loading. The hydrogel with high porosity can absorb the exudate on the ulcer surface promptly and quickly, keep the ulcer surface clean and breathable, and provide a good environment for the adhesion of active ingredients and drug delivery.

[0065] 3. Swelling ratio

[0066] The water absorption rate of the hydrogels in Comparative Example 1 and Example 2 at different time points was monitored to characterize the swelling rate of the hydrogels. Figure 5As shown. In the initial stage of swelling, the hydrogel rapidly absorbs water and swells, and the swelling rate increases rapidly. After about 20 hours, the swelling rate of the hydrogel gradually slows down and tends to equilibrium. Both hydrogels can absorb a large amount of water and reach swelling equilibrium at about 450-500%. The addition of FeNPs@DaochiSan will not affect the swelling rate of the hydrogel. The expansion of the polymer leads to an increase in surface contact and mechanical entanglement, thereby promoting hydrogen bond interactions between the polymer and the mucosal network. The swelling ability of the nanocomposite hydrogel is affected by the hydrophilicity of chitosan, which enhances the porosity and surface area of ​​the structural network, thereby increasing the swelling ratio of the hydrogel. A high swelling ratio is conducive to better adhesion of the hydrogel to the ulcer surface, avoiding drug loss and improving the therapeutic effect.

[0067] 4. Adhesion time

[0068] The results are as follows Figure 6 As shown, the average adhesion time of comparative example 1 is 23.8 minutes, and the adhesion time of example 2 is significantly higher than that of comparative example 1, which is beneficial to increase the contact time between the ulcer surface and the drug and better exert the therapeutic effect of the drug. The swelling ratio and viscosity properties of the polymer have a strong correlation with the time-dependent adhesion ability of the hydrogen bond.

[0069] 5. In vitro antioxidant capacity

[0070] Vitamin C was used as a positive control group to conduct DPPH scavenging rate, hydrogen peroxide scavenging rate, and nitric oxide free radical scavenging rate experiments with the hydrogel of Example 2. In the DPPH scavenging rate experiment, the concentration of Vc and the hydrogel of Example 2 was 2.5 μg / mL to 25 μg / mL; in the hydrogen peroxide scavenging rate experiment, the concentration of Vc and the hydrogel of Example 2 was 0.75 μg / mL to 7.5 μg / mL; in the nitric oxide free radical scavenging rate experiment, the concentration of Vc and the hydrogel of Example 2 was 0.75 μg / mL to 7.5 μg / mL.

[0071] The results are as follows Figure 7-Figure 9 shown. Figure 7 is the DPPH clearance rate, Figure 8 is the hydrogen peroxide clearance rate, Fig. 9 The result shows that the free radical neutralization effect of Example 2 is dose-dependent, and it has a good scavenging effect on various free radicals, especially for the hydrogen peroxide scavenging rate and the nitric oxide free radical scavenging rate. The scavenging effect of the hydrogel in Example 2 is similar to that of Vc, showing a strong in vitro antioxidant ability.

[0072] 6. Cytotoxicity

[0073] The toxicity of the hydrogels of Comparative Example 1 and Example 2 to human gingival fibroblasts was tested by MTT method, and the specific process is as follows:

[0074] a) Cultivation of human gingival fibroblasts: 96-well cells were plated at a density of 5 × 10 4 Cells at 1000 cells / mL were coated on culture plates and cultured for 12 hours.

[0075] b) The sample was dissolved in DMSO, added to a culture dish, and after plating and washing for 12 hours, divided into three groups, including: (I) a blank control group (Control): a cell culture medium containing no hydrogel in the cell culture; (II) a cell culture medium containing the hydrogel of Comparative Example 1 in the cell culture; (III) a cell culture medium containing the composite hydrogel of Example 2 in the cell culture.

[0076] c) Each well was treated with different types of culture media (I-III) and incubated for 48 hours at 5% CO2 and 37°C. After trypsinization of the cells, 200 μL of the cell suspension was mixed with 40 μL of 0.4% Thiazolyl blue and suspended by Neubauer Lamela for 3 minutes.

[0077] d) Measure the absorbance of each well using an enzyme-linked immunosorbent assay (ELISA) reader.

[0078] e) Calculation of cell viability: According to cell viability = number of unstained cells / total number of cells, the cell viability of the sample was determined.

[0079] The results are as follows Fig.10 As shown, the hydrogel of comparative example 1 has no cytotoxic effect, while example 2 with the addition of FeNPs@DaochiSan particles not only has no cytotoxic effect, but also can improve the biocompatibility of cells and promote cell growth.

[0080] In summary, the present invention adds flavored hematogenous iron nanoparticles into pure hydrogel, and the obtained FeNPs@DaochiSan gel has good controllable bioadhesion properties and mechanical strength; at the same time, FeNPs@DaochiSan gel has excellent biological activity and biocompatibility, and has extremely high application value in local drug concentration, anti-oxidation, antibacterial, wound protection, and accelerated repair, especially in the treatment of oral ulcers.

[0081] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a traditional Chinese medicine nano hydrogel for treating recurrent oral ulcers, characterized in that: The steps include: (1) preparing flavored hematite nanoparticles; (2) preparing sodium alginate solution and chitosan solution; (3) After mixing the sodium alginate solution and the chitosan solution, add the solution of the flavored hematite nanoparticles to obtain a composite hydrogel solution, which is dried and formed to obtain the traditional Chinese medicine nano hydrogel.

2. The preparation method according to claim 1, characterized in that: The method for preparing the flavored hematite nanoparticles comprises the following steps: a. Mix bamboo leaves, raw rehmannia root, tongcao, raw licorice root and raw gypsum in a mass ratio of (12-18): (8-12): (8-12): (4-8): (25-40) and grind into powder, dissolve the powder in boiling water to obtain a modified Daochi powder solution; b. Mix the flavored red-dispersing powder solution and the FeCl3·6H2O solution in an ultrasonic bath for reaction, centrifuge, and dry to obtain the flavored red-dispersing powder iron nanoparticles.

3. The preparation method according to claim 2, characterized in that: The concentration of the Jiawei Daochisan solution is 1.5-3 mg / mL; the concentration of the FeCl3·6H2O solution is 0.01-0.03 M; the volume ratio of the Jiawei Daochisan solution to the FeCl3·6H2O solution is 10:(2-5).

4. The preparation method according to claim 2, characterized in that: The temperature of the ultrasonic bath is 60°C-70°C, the time is 60-80 minutes, and the ultrasonic power is 200-250W.

5. The preparation method according to claim 1, characterized in that: The sodium alginate solution is obtained by mixing sodium alginate and water in a ratio of 1 g: (40-60) mL.

6. The preparation method according to claim 1, characterized in that: The chitosan solution is obtained by mixing chitosan, glacial acetic acid and water in a ratio of 1 g: (2-6) mL: (240-260) mL.

7. The preparation method according to claim 1, characterized in that: The volume ratio of the sodium alginate solution and the chitosan solution when mixed is 1:1, and the mixing time is 25-40 minutes.

8. The preparation method according to claim 1, characterized in that: The concentration of the flavored hematite nanoparticle solution is 1 mg / mL, and the added amount is 45-55 mL.

9. A traditional Chinese medicine nano hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the traditional Chinese medicine nano-hydrogel according to claim 9 in preparing a product for treating recurrent oral ulcers.

Citation Information

Cited By

  • Oral care essential oil for repairing oral mucosa and preparation method of oral care essential oil

    CN121041166A